STUDY OF GEOMAGNETIC MICROPULSATIONS. - Wilson,Charles R.; Annexstad,John O. (1966)
Over 800 vector diagrams representing the locus of end points of the perturbation vector in three orthogonal planes (H-D, H-Z, D-Z) were constructed from the rapid run magnetograms of Pg micropulsations observed at College, Alaska and Macquarie Island during 1963 and 1964. The characteristics of Pg's as noted from these vector diagrams are the sense of rotation of the perturbation vector, the shape and orientation of the vector diagrams, and the symmetry relationships between the vector diagrams at conjugate points. The physical characteristics of Pg events observed at conjugate points that were investigated are time and frequency of occurrence, period and amplitude of the components, power spectral density and dispersion of the waves. The vector diagrams of Pg micropulsations are related to the vector diagrams predicted by a model of a rotating ionospheric current induced by standing transverse hydromagnetic waves. The predictions of this model agree with the observed shapes and orientations of the vector diagrams and the sense of rotation of the perturbation vector in the three orthogonal planes of Pg events. The characteristics of the Pg micropulsation as determined in this thesis indicate that Pg's are caused by transverse hydromagnetic waves propagating along the field lines to high latitude conjugate points. (Author)